Modeling Unstratified Burials via Bayesian Analysis with Log-Normal Interval Priors. Issue 4 (27th May 2019) - Kidd, R S
ABSTRACT: Tombs and cairns present a dating challenge when the human remains are unstratified, incomplete and dispersed. By considering the distribution of time intervals between deaths as a possible a priori condition of multiple burials of select groups, a Bayesian model is suggested that may constrain the uncertainty date range of the group. The method may also address the wide uncertainties seen in radiocarbon calibration on a calibration curve plateau. The mathematical justification for the choice of Log Normal intervals, between death events, is first presented, followed by worked examples that compare the treatment of groups of 22 dates using Phase then Sequence with interval gaps. Finally, scenarios of potential Select Groups are examined, to demonstrate the efficacy of this alternative heuristic model to current model treatments.